Workplace harassment is associated with differences in personality traits, coping strategies and work ability: cross sectional study among healthcare professionals - Vivarelli, Silvia; Oliveri, Caterina; Savasta, Saveria; Fiorino, Francesca Simona; Fenga, Concettina (Frontiers in Public Health, 2025)
IntroductionWorkplace Harassment (WPH) in the healthcare sector remains a critical global issue, adversely affecting employees’ psychological well-being and work ability.AimThis study investigated gender differences, variations in personality traits and coping strategies linked to WPH, and the impact of these dynamics on work performance of healthcare workers (HCW).MethodsA cross-sectional survey was administered to a sample of 415 HCW (138 men and 277 women), including physicians, nurses, and other staff members (e.g., administrative, technical, and auxiliary personnel). Participants completed a series of standardized instruments: WPH and Health Survey Questionnaire (WHHSQ), Mini International Personality Item Pool (Mini-IPIP), Brief-COPE inventory, and Work Ability Index (WAI).ResultsReports of WPH within the past 12 months showed a significantly higher prevalence among women (36.2%, n = 94) compared to men (23.3%, n = 31), p < 0.01. Verbal abuse (30.4%) and bullying/mobbing (17.1%) were the most common forms, with supervisors implicated in about 10–15% of cases. Informal handling, such as confiding in colleagues or family (20–30%), was far more frequent than formal reporting (8–10%). Females scored higher in Agreeableness (M = 16.26 vs. 15.29, p < 0.001) and Conscientiousness (M = 15.03 vs. 14.01, p < 0.001) but lower in Neuroticism (M = 11.56 vs. 12.93, p < 0.0001) compared to males. Individuals who experienced harassment, exhibited lower Neuroticism (mean = 11.28 vs. 12.37, p < 0.0001) than non-harassed peers. Coping patterns varied: women reported greater use of Seeking Social Support strategies (M = 17.80 vs. 16.02, p < 0.0001), while harassed individuals relied more on Avoidance strategies (M = 19.15 vs. 18.16, p < 0.05), including self-distraction and substance use. Men had higher work ability scores than women (χ2 = 8.799, p < 0.05), while WPH was linked to a significant reduction in work ability (χ2 = 15.729, p < 0.01).ConclusionWomen are likely to face higher WPH rates and tend to seek social support more frequently, while harassed individuals, regardless of gender, increasingly rely on avoidance coping. Exposure to WPH is associated with decreased work ability. Low rate of formal reporting reveals systemic gaps in institutional responses. To address these challenges, healthcare organizations should implement comprehensive risk assessment strategies incorporating gender-specific factors and psychological profiles to identify vulnerable staff earlier. Enhancing reporting systems, offering proactive psychological support, and promoting adaptive coping strategies are essential to reduce harm, foster resilience, thereby creating safer and healthier work environments.